Separating cells - Patel, D. (Oxford : BIOS ; New York : Springer, 2001)
Separating Cells: The basics provides user-friendly and practical guidance to the techniques most commonly used to separate cells.
Preparation of cell suspensions -- Fractionation of cells by sedimentation methods -- Centrifugal elutriation -- Free-flow electrophoresis -- Affinity separation -- Flow cytometry.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Cell separation -- Laboratory manuals; Cell Separation -- methods; Cellules -- Séparation -- Manuels de laboratoire; SCIENCE -- Life Sciences -- Cell Biology; Cell separation; Andre fag (naturvidenskab og teknik) -- Andre fag; Electronic books; Laboratory Manual; Laboratory manuals; Laboratory manuals; Manuels de laboratoire